(3Odjd GdeJYGedjf aj HhQUI GdChQGb GdeGdjI (B/s - (3GdfLGQ, YfGjGJs ((3GdbGgQI(B: s (3GdefXeI GdYQHjI ddJfejI GdGOGQjI(B, s, 2006)
(3jVe HhQUI GdGhQGb GdeGdjI hhVYgG Ydi NQjWI GShGb GdeGd, GdGOhGJ GdeGdjI GdeJOGhdI aj GdHhQUI, GdGSJKeGQ aj GdGhQGb GdeGdjI gh GSJKeGQ bGFe Ydi GdeYQaI, YedjGJ GdJOGhd aj GdHhQUI, GdfMGaX hUfGOjb GdGSJKeGQs
Keywords: (3GdGhQGb GdeGdjIs; (3GdHhQUIs